Integrasi Green Accounting dan Carbon Policy dalam Maqashid Shariah Index : Mewujudkan manifestasi akuntansi syariah Rahmatan Lil Alamin - Ikhsan Alfarizi; Mukhtaruddin . (GLOBAL SCIENTS PUBLISHER, 2026)
The global climate crisis demands a transformation of economic regulations through carbon policies and sustainable accounting practices. This article aims to analyze the integration of green accounting and carbon policy in enchancing the maqashid shariah index (MSI) performance as a manifestation of rahmatan lil alamin shariah accounting. Using the systematic literature review (SLR) method on 31 scientific articles from 2021 – 2026, this research integrates shariah enterprise theory (SET), legitimacy theory, and signalling theory. The result show that green accounting positively affects the MSI, particularly in the maslahah dimension through enviromental protection (hifdz al-bi’ah). Compliance with carbon policies, such as carbon taxes, is viewed as a form of obedience to ulul amri to prevent destruction (fasad). However, challenges such as greenwashing persist due to legitimacy pressures and financial constraints. This article emphasizes the importance of strengthening islamic corporate governance to ensure honesst and transparent sustainability reporting.